Zastosowanie Google Maps API do multimedialnej wizualizacji informacji o obiektach przestrzennych w internecie - Halik, Łukasz (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2011)
The present article presents Google Maps API, which is an Internet application providing access to cartographic services and technology. Owing to the application of relevant procedures and programming commands it has been used as a link combining various forms of multimedial presentation that were discussed in the article in the results of studies. A visualization system of geoinformation has been created, composed of three information levels. The author of this paper, as a participant of the Internet community, finds satisfaction that through his research he added another brick for creation of a virtual image of reality on the Internet.
Keywords: Google Map API; Multimedial visualisation; Internet cartography